Improvement compressive strength of cementitious composites in different curing media by incorporating ZrO2 nanoparticles - Mohammad Hossein Rafieipour; Ali Nazari; Mohammad Ali Mohandesi; Gholamreza Khalaj (Materials Research, 2012)
In the present work, the effect of curing medium on microstructure, physical, mechanical and thermal properties of ZrO2 nanoparticles blended concrete has been investigated. ZrO2 nanoparticles were partially used instead of cement by 0.5, 1.0, 1.5 and 2.0 weight percent. Curing of the specimens was carried out in water and saturated limewater for 7, 28 and 90 days. The results indicate that ZrO2 nanoparticles up to maximum of 2.0% produces cementitious composite with improved compressive strength by curing in saturated limewater. The optimum level of replacement for the specimens cured in water was 1.0 weight percent. ZrO2 nanoparticles can improve the filler effects and also the high activity of fine particles substantially increases the quantity of strengthening gel. Although the limewater reduces the strength of concrete without nanoparticles when compared with the specimens cured in water, curing the specimens in saturated limewater results in more strengthening gel formation around ZrO2 nanoparticles blended concrete causes high strength.